QuickBooks online for dummies - Marmel, Elaine J. (--For dummies., 2016)
Keep your business finances under control with QuickBooks Online! Want to manage your financial records in the Cloud-without losing your cool? It's quicker and easier than you think! This new edition of QuickBooks Online For Dummies offers everything you need to use the world's most popular software for fast and easy mobile accounting-no outside help required! Inside, you'll find hands-on, practical guidance for using QuickBooks Online to build the perfect budget, process payroll, simplify your tax return preparation, create invoices and credit memos, manage inventory, and so much more. QuickBooks liberated small business owners, accountants, and bookkeepers from being chained to their desks with ledgers and journals. And now, QuickBooks Online liberates them once more, bringing all the software's convenient tools to any Internet browser, giving anyone with business finance responsibility the freedom to access the books on any device, at any time. QuickBooks Online For Dummies takes the intimidation out of this new technology and shows you how to make it work-painlessly and productively-for you and your small business. It doesn't get easier than that! Securely organize your finances in one place Use QuickBooks Online to take the stress out of tax season Create invoices, record sales receipts, and pay your bills Track inventory, figure job costs, and create reports to monitor your business If you're a small business owner, manager, or employee looking for a fast, affordable, convenient way to manage your company's finances, QuickBooks Online For Dummies has everything you need to get up and running fast.